Sistem Monitoring dan Kontrol Tangki Air Menggunakan Raspberry Pi Berbasis Bot Telegram - Amertha, Lanang Bagus; Hartati, Rukmi Sari; Sudarma, Made (Majalah Ilmiah Teknologi Elektro; Vol 21 No 2 (2022): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2022.v21i02.P02, 2022)
Water tanks are often placed at a height to take advantage of the force of gravity so that water can flow optimally. The high position of the water tank is difficult for users to find out the quality and volume of water. Poor water quality such as experiencing turbidity can have a bad impact. So we need a system that can detect turbidity and water volume and can inform users remotely. The technology that can be used is the internet of things. The system built will monitor the turbidity and volume of the user's water tank, as well as control the pump in the form of turning it on and off. The interaction process between users and the system using bots from Telegram. The test results of the system can monitor turbidity and water volume and control the water pump through interaction with users using Telegram bots. The test results show the average speed of the entire system process is 1.48 seconds. The use of Raspberry Pi microcontroller can be used for future system development such as adding cloudy water treatment process features or others. Another development suggestion by adding bots as an interface from other instant messaging applications.